Modeled Respiratory Tract Deposition of Smoke Aerosol from Conventional Cigarettes, Electronic Cigarettes and Heat-not-burn Products - Yawen Li; Huapeng Cui; Li Chen; Meijuan Fan; Junlan Cai; Junwei Guo; Caner U. Yurteri; Xiaoxi Si; Shaofeng Liu; Fuwei Xie; Jianping Xie (Aerosol and Air Quality Research)
Abstract Knowledge of the deposition of inhaled smoke aerosol in the human respiratory tract has great value for risk assessments of the inhalation toxicology of tobacco products. In this study, differential mobility spectrometry (DMS) was used to characterize smoke particles generated from a conventional cigarette, e-cigarette and heat-not-burn product. The aerosol properties obtained by DMS were then applied to a Multiple Path Particle Dosimetry (MPPD) model to predict the deposition of aerosol particles in the human respiratory tract. The DMS results showed that the particle size distribution of aerosol from the three products differed considerably, with a count median diameter of 14.2–25.4 nm, 50.6–55.3 nm and 172–179 nm for the e-cigarette, heat-not-burn product and conventional cigarette, respectively. However, there was no significant difference in the particle number concentration of aerosol from the three products. The MPPD model indicated that the total deposition fraction of aerosol particles from the e-cigarette and heat-not-burn product was higher than that from the conventional cigarette, and deposition of particles from the e-cigarette in the three human airway regions (head airway, tracheobronchial and pulmonary regions) was higher than that from the heat-not-burn product and conventional cigarette; the particle number concentration deposited in the pulmonary region was the highest, comprising more than 60% of total deposition. Lastly, among the lung lobes, the highest number deposition fraction occurred in the right lower lobe. The relationship between deposition fraction and airway generation was relatively similar among the three aerosols, and the highest deposition fraction occurred in the 20th to 23rd generation airways. The deposition results showed that smaller particles, such as those from the e-cigarette aerosol, were more easily deposited in the human respiratory tract. Combined with knowledge of the harmful aerosol constituents, these deposition data will provide important information for hazard evaluation of new tobacco products.